Toxicopathological changes on Wistar rat after multiple exposures to acetamiprid - S. Mondal; R. C. Ghosh; S.S. Karnam; Kamal Purohit (Veterinary World, 2014)
Aim: To see the toxicopathological changes after multiple exposure to acetamiprid (ACP) and also to obtain more information regarding the manner in which ACP acts at cellular level. Materials and Methods: A subacute toxicity study of ACP was undertaken in 72 female Wistar rats in four groups (18 each). Three different concentrations of ACP (25, 100 and 200 mg/kg of body weight) were administered orally to rats. Untreated rats served as control. Different plasma enzyme and analytes were measured. Gross and histopathological observations were noted in this experiment. Result: There was a significant increase in the plasma enzymes tested in this experiment. There was a significant decrease in plasma glucose, cholesterol and low-density lipid. Necrotic and degenerative changes were observed in vital organs. Conclusion: It is observed that ACP has the toxic potential (on liver, kidney, heart, ovary and brain) at sub lethal doses.